1998
DOI: 10.1128/aem.64.3.1115-1122.1998
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Copper Biochelates from Methylosinus trichosporium OB3b and Soluble Methane Monooxygenase Mutants

Abstract: Methylosinus trichosporium OB3b produces an extracellular copper-binding ligand (CBL) with high affinity for copper. Wild-type cells and mutants that express soluble methane monooxygenase (sMMO) in the presence and absence of copper (sMMOc) were used to obtain cell exudates that were separated and analyzed by size exclusion high-performance liquid chromatography. A single chromatographic peak, when present, contained most of the aqueous-phase Cu(II) present in the culture medium. In mutant cultures that were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…This paper is also the first report of a second CBC, CBC-L 2 , which may have been present as a contaminant in previous CBC preparations from M. capsulatus Bath. One or both of the CBCs appear to be the same copper-complexing agent partially purified by Téllez et al (55). Lastly, this report describes the effect of the copper concentration in the culture medium on copper uptake, the expression of both MMOs, and extracellular concentration of the CBC in wild-type and sMMO C mutant strains of M. trichosporium OB3b.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…This paper is also the first report of a second CBC, CBC-L 2 , which may have been present as a contaminant in previous CBC preparations from M. capsulatus Bath. One or both of the CBCs appear to be the same copper-complexing agent partially purified by Téllez et al (55). Lastly, this report describes the effect of the copper concentration in the culture medium on copper uptake, the expression of both MMOs, and extracellular concentration of the CBC in wild-type and sMMO C mutant strains of M. trichosporium OB3b.…”
mentioning
confidence: 60%
“…The Nterminal amino acid sequence of CBC-L 2 , SPMP?S, differed from that of CBC-L 1 . The amino acid compositions of both CBCs show some similarity, especially in the multiple S, to the iron-chelating pseudobactins, ferribactins, and pyoverdins produced by some species of Pseudomonas and Azotobacter (20,53,55) but showed no sequence similarities. Unlike many iron-binding polypeptides, the identified amino acids of both CBCs are all L-amino acids (20,53,58).…”
Section: Isolation Of Cbcmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, because pMMO activity was lost when CBCs were removed from the pMMO polypeptides, it was suggested that CBCs may function as a cofactor for its activity or stability, scavenge oxygen radicals, as well as fulfilling possible secondary roles previously mentioned. Earlier that same year, Téllez et al (1998) isolated what they referred to as a copper-binding ligand (CBL) from M. trichosporium OB3b, thought to be a same compound described by DiSpirito et al (1998). This study described a ~500-MW compound that had a ligand preferring copper over nickel despite 20-fold concentrations of the latter.…”
Section: Chronological Characterization Of Methanobactinmentioning
confidence: 97%
“…Methanobactin is known to play a significant role in the copper-switch that controls expression of the two forms of MMO. Indeed, the first form of methanobactin characterized was from Methylosinus trichosporium OB3b (Figure 1-8), and it was found to be a small modified polypeptide of 1,154 Da (DiSpirito et al 1998;Tellez et al 1998;Kim et al 2004). Reprinted with permission from (Semrau et al 2013).…”
Section: Methane-oxidizing Bacteria 13mentioning
confidence: 99%